Sosialisasi Blended Learning dalam Pembelajaran Bahasa Inggris - Elyza Martiarini; Asti Ramadhani Endah Lestari (Jurnal PkM Pengabdian kepada Masyarakat, 2020)
The aim of this program is to provide socialization of Blended Learning in the revolutionary era 4.0 for the teachers or instructors at Yasporbi III. The program focused on training the teacher on how to use Google Classroom application. The advantage of Google Classroom application lies on the flexibility and effectiveness of learning. This socialization activity provided knowledge to all participants about Learning Management Systems that could be used to support digital media-based learning with the theme of Blended Leaning which is very suitable for the development of this disruptive era.